In‐person interventions to reduce social isolation and loneliness: An evidence and gap map - Vivian Welch; Elizabeth Tanjong Ghogomu; Sierra Dowling; Victoria I. Barbeau; Ali A. A. Al‐Zubaidi; Ella Beveridge; Mostafa Bondok; Payaam Desai; Rebecca Doyle; Jimmy Huang; Tarannum Hussain; Alyssa Jearvis; et al. (Campbell Systematic Reviews, 2024)
Abstract Background Social isolation and loneliness can occur in all age groups, and they are linked to increased mortality and poorer health outcomes. There is a growing body of research indicating inconsistent findings on the effectiveness of interventions aiming to alleviate social isolation and loneliness. Hence the need to facilitate the discoverability of research on these interventions. Objectives To map available evidence on the effects of in‐person interventions aimed at mitigating social isolation and/or loneliness across all age groups and settings. Search Methods The following databases were searched from inception up to 17 February 2022 with no language restrictions: Ovid MEDLINE, Embase, EBM Reviews—Cochrane Central Register of Controlled Trials, APA PsycInfo via Ovid, CINAHL via EBSCO, EBSCO (all databases except CINAHL), Global Index Medicus, ProQuest (all databases), ProQuest ERIC, Web of Science, Korean Citation Index, Russian Science Citation Index, and SciELO Citation Index via Clarivate, and Elsevier Scopus. Selection Criteria Titles, abstracts, and full texts of potentially eligible articles identified were screened independently by two reviewers for inclusion following the outlined eligibility criteria. Data Collection and Analysis We developed and pilot tested a data extraction code set in Eppi‐Reviewer. Data was individually extracted and coded. We used the AMSTAR2 tool to assess the quality of reviews. However, the quality of the primary studies was not assessed. Main Results A total of 513 articles (421 primary studies and 92 systematic reviews) were included in this evidence and gap map which assessed the effectiveness of in‐person interventions to reduce social isolation and loneliness. Most (68%) of the reviews were classified as critically low quality, while less than 5% were classified as high or moderate quality. Most reviews looked at interpersonal delivery and community‐based delivery interventions, especially interventions for changing cognition led by a health professional and group activities, respectively. Loneliness, wellbeing, and depression/anxiety were the most assessed outcomes. Most research was conducted in high‐income countries, concentrated in the United States, United Kingdom, and Australia, with none from low‐income countries. Major gaps were identified in societal level and community‐based delivery interventions that address policies and community structures, respectively. Less than 5% of included reviews assessed process indicators or implementation outcomes. Similar patterns of evidence and gaps were found in primary studies. All age groups were represented but more reviews and primary studies focused on older adults (≥60 years, 63%) compared to young people (≤24 years, 34%). Two thirds described how at‐risk populations were identified and even fewer assessed differences in effect across equity factors for populations experiencing inequities. Authors’ Conclusions There is growing evidence that social isolation and loneliness are public health concerns. This evidence and gap map shows the available evidence, at the time of the search, on the effectiveness of in‐person interventions at reducing social isolation and loneliness across all ages and settings. Despite a large body of research, with much of it published in more recent years, it is unevenly distributed geographically and across types of interventions and outcomes. Most of the systematic reviews are of critically low quality, indicating the need for high quality reviews. This map can guide funders and researchers to consider the areas in which the evidence is lacking and to address these gaps as future research priorities.